USE OF INTERACTIVE METHODS (ROUND TABLE DISCUSSION AND BUSINESS GAME) AND THEIR EFFECTS - Kurbanova, M.A. (SCIENCE and SOCIETY, 2022)
The use of interactive methods in the process of educating and educating the younger generation is a purposeful effort to achieve a comprehensive, convenient and high-quality result. The first method of scientific work is the method of round table discussion, which is widely used among interactive methods and is distinguished by its effectiveness, and its application and coverage of its achievements and a method that develops speaking related to social life and business to illuminate the effects of a business game constitute the goals and objectives of scientific work.
Keywords: interactive teaching methods; round table; business games; skill; technology